The Effect of Bituminous and Lignite Ash on the Performance of Ilmenite as Oxygen Carrier in Chemical‐Looping Combustion. Issue 9 (22nd August 2013) - Azis, M. M.; Leion, H.; Jerndal, E.; Steenari, B.‐M.; Mattisson, T.; Lyngfelt, A.; Epple, Bernd
Abstract The influence of ash in chemical‐looping combustion (CLC) has been studied in a lab‐scale fluidized bed reactor. The oxygen carrier, ilmenite, was investigated with German lignite coal, Chinese bituminous coal, Mexican pet coke, wood char, and methane. Lignite ash and ash from gasified Chinese bituminous coal were compared in this study. Up to 50 wt % and 33.3 wt % loadings of ash from the combustion of lignite and ash from the gasification of coal were added. The gas conversion was clearly affected by the addition of ash, and very similar results were seen both for methane conversion and for CO conversion in the solid fuel tests. Thus, both ashes showed initial decrease in gas conversion with the addition of some ash due to the presence of inert/deactivating material in the ashes. At higher ash loading, a beneficial effect of ash could be seen. Furthermore, no negative effect of ash addition on the fluidizability of the bed material could be seen.